Unelongated Stems are an Active Nitrogen-Fixing Site in Rice Stems Supported by Both Sugar and Methane Under Low Nitrogen Conditions - Takanori Okamoto; Yukina Hotta; Rina Shinjo; Yoko Masuda; Arisa Nishihara; Ryosuke Sasaki; Masami Yokota Hirai; Reo Nishiwaki; Sota Miyado; Daisuke Sugiura; Motohiko Kondo (Rice)
Abstract Enhancing nitrogen (N) fixation in rice plants can reduce N fertilizer application and contribute to sustainable rice production, particularly under low-N conditions. However, detailed microbial and metabolic characterization of N fixation in rice stems, unlike in the well-studied roots, has not been investigated. Therefore, the aim of this study was to determine the active N-fixing sites, their diazotroph communities, and the usability of possible carbon sources in stems compared with roots. The N-fixing activity and copy number of the nitrogenase gene in the rice stem were high in the outer part of the unelongated stem (basal node), especially in the epidermis. N fixation, estimated using the acetylene reduction assay, was also higher in the leaf sheath and root than in the inner part of the unelongated stem and culm. Amplicon sequence variants (ASVs) close to sugar-utilizing heterotrophic diazotrophs belonging to Betaproteobacteria and type II methanotrophic diazotrophs belonging to Alphaproteobacteria were abundant in the outer part of the unelongated stems. Media containing crushed unelongated stems exhibited N-fixing activity when sucrose, glucose, and methane were added as the sole carbon sources. This suggested that N fixation in the unelongated stems was at least partly supported by sugars (sucrose and glucose) and methane as carbon sources. ASVs close to sugar-utilizing heterotrophs belonging to Actinobacteria were also highly abundant in the unelongated stem; however, their functions need to be further elucidated. The present finding that diazotrophs in rice stems can use sugars such as sucrose and glucose synthesized by rice plants provides new insights into enhancing N fixation in rice stems.